Nitrogênio e Potássio na Formação, Produção e Incidência de Pragas na Cultura do Morangueiro - Santos, Oliveiros Miranda dos (2010)
Furthermore, the characteristics of the fruit of strawberry (to be consumed "in natura") immediately after the harvest and the attractiveness that it has on consumers for children, this may be a good economical choice, enriched with a good dose of compromise with human health and environmental responsibility to produce strawberries without the use of pesticides and adequate application of nutrients minerals. The production of strawberry (Fragaria x ananassa Duchesne). Has great importance for the Southern and Southeastern Brazil with the culture, and the State of Minas Gerais as the largest producer. Awareness of the risks of pesticide use in this culture has led to the development and improvement of production systems. Besides the action of environmental factors acting on the physiology of the crop, fertilization is another factor that interferes with the production and fruit quality. The mineral nutrition seems to be a decisive factor in the resistance of plants against pests. Within all the plagues of the strawberry mite Tetranychus urticae twospotted is a pest, which may reduce the yield by 80% when not controlled. This work was performed at IFSULDEMINAS - Campus Inconfidentes and aimed to assess the effect of fertigation of nutrients nitrogen and potassium in different dosage, training, production and incidence of pests on strawberry plants of cultivar Oso Grande '. The experiment was mounted in an area of 132.5 square meters, with 780 plants. We applied the randomized block design with five treatments and four replications, each plot comprised 15 plants. During the cycle plants received different doses in fertigation. The arthropod pests were identified and counted, held weighing fruit, shoots and roots of plants and loss of fruit weight. The results showed that both excess and lack of N and K are harmful plants both in production and in the incidence of pests, demonstrating that a more balanced treatment 200, 400 kg / ha of N and K is presented the best answer to production, fruit quality and lower incidence of insects on strawberry culture.